Analysing the socioeconomic and motivational factors affecting the willingness to pay for climate change adaptation in Malaysia - Al-Amin A.Q.; Masud M.M.; Kabir Sarkar M.S.; Filho W.L.; Doberstein B. (Elsevier Ltd, 2023)
The main purpose of this article is to shed light on the processes leading to a climate change adaptation policy by estimating the socioeconomic and motivational factors affecting farmers willingness to pay (WTP) for an adaptation program. This study was conducted in North-West Selangor, Malaysia to examine the WTP of farmers for climate change adaptation in the agriculture sector. Data was collected from 385 farmers in the Integrated Agricultural Development Area through face-to-face interview. A contingent valuation method (CVM) was applied as a mechanism to quantify the factors affecting WTP. This study identified that socioeconomic factors and motivational aspects act as predictors to engage in WTP for an adaptation program. The findings indicated that several factors influence the WTP for a planned adaptation program, such as the income of the farmer (? = 0.363), their education level (? = 0.1.638), farm size (? = 0.341), household size (? = 0.293), concern about environmental protection irrespective of cost (? = 0.260), climatic impact on agricultural production (? = 0.421) and risk concerns due to climate change (? = 0.229). The findings describe the relevance and preferences related to WTP for the implementation of the correct adaptation policies. This study should help national policymakers to take appropriate decisions for planned adaptation programs in Malaysia. 2020